HUBUNGAN DUKUNGAN ORANG TUA DENGAN MOTIVASI BELAJAR SISWA KELAS V SEKOLAH DASAR NEGERI DI KELURAHAN CAKUNG TIMUR, JAKARTA TIMUR - Fitri Hapsari, Annisa; Winarni, Susi; Syarif Sumantri, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between parental support and the learning motivation of fifth-grade students at public elementary schools in Cakung Timur, East Jakarta. The background of the study is based on the low level of parental involvement in children's education, which affects students' learning motivation. The research method used is correlational quantitative, with a sample of 120 students selected using a simple random sampling technique. The results of data analysis show a significant positive relationship between parental support and learning motivation, with a Pearson correlation coefficient of 0.612 and a significance value of 0.001 (< 0.05). The coefficient of determination indicates that 37.4% of the variance in learning motivation is influenced by parental support, while the remaining percentage is influenced by other factors. These findings indicate that the higher the level of parental support, the higher the students’ learning motivation.